2009
DOI: 10.1007/s11069-009-9348-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cyclogenesis parameter for developing and nondeveloping low-pressure systems over the Indian Sea

Abstract: A cyclone genesis parameter, termed the genesis potential parameter (GPP), for the Indian Sea is proposed. The parameter is defined as the product of four variables, namely vorticity at 850 hPa, middle tropospheric relative humidity, middle tropospheric instability, and the inverse of vertical wind shear. The variables are calculated using the National Centers for Environmental Prediction (NCEP), USA, reanalysis data, averaged within a circle of 2.5°radius around the centre of cyclonic system. The parameter is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…This provides useful information which has direct relevance to disaster management preparedness and other activities such as transportation, tourism, and fishing. Recently, Kotal et al (2009a) further extended the work and suggested another genesis potential parameter which takes into account both dynamical and thermodynamical factors. Kotal et al (2009a) incorporated some thermodynamical parameters such as lapse rate and middle tropospheric moisture in addition to the dynamical parameters which are already included in the study of Roy Bhowmik (2003).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This provides useful information which has direct relevance to disaster management preparedness and other activities such as transportation, tourism, and fishing. Recently, Kotal et al (2009a) further extended the work and suggested another genesis potential parameter which takes into account both dynamical and thermodynamical factors. Kotal et al (2009a) incorporated some thermodynamical parameters such as lapse rate and middle tropospheric moisture in addition to the dynamical parameters which are already included in the study of Roy Bhowmik (2003).…”
Section: Introductionmentioning
confidence: 97%
“…Various stages of cyclone forecasting are: (a) genesis, (b) track, and (c) intensity. In a series of recent studies, Kotal et al (2008Kotal et al ( , 2009aKotal et al ( , 2009b proposed an NWP-based objective method for handling various stages of cyclone forecasting over the Bay of Bengal. The method was applied for real-time forecasting of tropical cyclone Nargis of May 2008, and the performance results are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Convective System Genesis Parameter (CSGP) is a new modified index and it is different from 180 the Genesis Parameter (GP) defined by Zehr (1992) and the Genesis Potential Parameter (GPP) 181 defined by Kotal (2009). We use the dynamical parameters defined by Zehr (1992), the humidity 182 parameter defined by Kotal (2009) and the Convective Instability parameter defined by Gray, 183 (1975).…”
mentioning
confidence: 99%
“…We use the dynamical parameters defined by Zehr (1992), the humidity 182 parameter defined by Kotal (2009) and the Convective Instability parameter defined by Gray, 183 (1975). Hence the revised index is a product of five parameters and it is defined as 184 Nat.…”
mentioning
confidence: 99%